PhI(OAc)2-mediated oxidative CH sulfoximination of imidazopyridines under mild conditions. Issue 1 (2nd January 2020) - Luan, Nannan; Liu, Zhenwei; Han, Shuaijun; Shen, Linhua; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Graphical abstract: Highlights: The sulfoximination of imidazopyridines at C3 position was firstly achieved. PhI(OAc)2 was used as oxidant. The reaction proceeds under air without metal catalyst. This method features mild conditions and good substrate tolerance. Abstract: A facile protocol for direct oxidative CN bond coupling of unactivated imidazo[1, 2- a ]pyridines with NH-sulfoximines was disclosed using sulfoximines as the nitrogen sources in the presence of (diacetoxy)iodobenzene (PhI(OAc)2 ). The reaction proceeded smoothly under air without any metal catalyst to give a series of C-3 sulfoximidoyl-functionalized imidazo[1, 2- a ]pyridines products regioselectively.